The Impact of Financial Structure and Liquidity on Tax Avoidance: The Moderating Role of Institutional Ownership in Indonesia’s Consumer Goods Sector - Pertiwi, Citra; Waluyo, Waluyo; Putra, Yananto Mihadi (Inisiatif Masyarakat Jurnal Indonesia (IMAJI), 2024)
This study aims to analyze the influence of Thin Capitalization, Profitability, and Liquidity on Tax Avoidance, as well as evaluate the role of institutional ownership moderation in these relationships in consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2022 period. The formulation of the problems raised in this study includes whether Thin Capitalization, Profitability, and Liquidity affect Tax Avoidance and whether Institutional Ownership can moderate the influence of these three variables on Tax Avoidance. This study uses a quantitative method with a causality approach. The data used is secondary data obtained from the company's financial statements, which are analyzed using multiple linear regression and moderate regression analysis (MRA). The results show that Thin Capitalization has a negative and significant influence on Tax Avoidance, while Profitability has no significant influence. Liquidity also has a negative and significant effect on Tax Avoidance. Furthermore, institutional ownership was proven to moderate the influence of profitability on tax avoidance significantly, but it did not significantly moderate the influence of thin capitalization and liquidity. The implications of this study are the importance of considering capital structure and liquidity in corporate tax management, as well as the role of institutional supervision in strengthening the influence of profitability on tax avoidance decisions. The latest of this research lies in incorporating the moderation variables of Institutional Ownership in analyzing the influence of financial factors on Tax Avoidance, especially in the context of consumer goods sector companies in Indonesia.